Display of cell surface sites for fibronectin assembly is modulated by cell adherence to (1)F3 and C-terminal modules of fibronectin. - Jielin Xu; Eunnyung Bae; Qinghong Zhang; Douglas S Annis; Harold P Erickson; Deane F Mosher (PLoS ONE)
Background Fibronectin-null cells assemble soluble fibronectin shortly after adherence to a substrate coated with intact fibronectin but not when adherent to the cell-binding domain of fibronectin (modules (7)F3-(10)F3). Interactions of adherent cells with regions of adsorbed fibronectin other than modules (7)F3-(10)F3, therefore, are required for early display of the cell surface sites that initiate and direct fibronectin assembly. Methodology/principal findings To identify these regions, coatings of proteolytically derived or recombinant pieces of fibronectin containing modules in addition to (7)F3-(10)F3 were tested for effects on fibronectin assembly by adherent fibronectin-null fibroblasts. Pieces as large as one comprising modules (2)F3-(14)F3, which include the heparin-binding and cell adhesion domains, were not effective in supporting fibronectin assembly. Addition of module (1)F3 or the C-terminal modules to modules (2)F3-(14)F3 resulted in some activity, and addition of both (1)F3 and the C-terminal modules resulted in a construct, (1)F3-C, that best mimicked the activity of a coating of intact fibronectin. Constructs (1)F3-C V0, (1)F3-C V64, and (1)F3-C Delta(V(15)F3(10)F1) were all able to support fibronectin assembly, suggesting that (1)F3 through (11)F1 and/or (12)F1 were important for activity. Coatings in which the active parts of (1)F3-C were present in different proteins were much less active than intact (1)F3-C. Conclusions These results suggest that (1)F3 acts together with C-terminal modules to induce display of fibronectin assembly sites on adherent cells.